Structures and Magnetic Properties of Al-Doped Fen (n = 2-7) Clusters: A DFT Study - Yu , Shuaiqin; Jia, Xiangfeng; Dong, Lihua; Yin, Yansheng (Asian Journal of Chemistry, 2010)
The structures and magnetic properties of aluminum doped Fen (n = 2-7) clusters have been systematically studied at the BPW91 level in density-functional theory (DFT). Calculated results show that an Al impurity does not change the ground-state structure of small iron cluster and prefers to occupy surface site bonding with iron atoms as many as possible. The total magnetic moments of Fen-1Al clusters is smaller than those of corresponding iron clusters due to the antiferromagnetic coupling between Fe and Al. The natural population and natural electron configurations are performed to analyze the main reason of the total magnetic moments decreased.